«Специальная военная операция» и языковая концептуализация действительности - Levontina, Irina; Šmeleva, Elena (Wiener Slawistischer Almanach, 2024)
This paper deals with the influence of the Russian “special military operation” in Ukraine at the Russian language; the shifts in the linguistic conceptualization of the world receive special attention. The paper discusses changes in the Russian traditional system of metaphors, the emergence of new words and new lexical groups, changes in the evaluative connotations of lexical units, as well as the implicatures of the choice of the Russian language as the means of communication. The research relies on the analysis of the modern Russian media, poetry, social networks, and messengers (both pro-governmental and oppositional) with special reference to the phenomena of hate speech, manipulation, and propaganda. In addition, the paper contains a comparison of the results of “Word of the Year 2022” contest for different languages in different countries.